Distinguishing the hydrologic regimes and vegetation of fens and wet meadows in the Rocky Mountains - Driver, Katharine M., author; Cooper, David J. (David Jonathan), 1952-, advisor; Baron, Jill, committee member; Kelly, Eugene Francis, committee member; Schweiger, E. William, committee member (Colorado State University. Libraries, 2010)
Fens and wet meadows in the Rocky Mountains are groundwater fed wetlands that are infrequent on the landscape but critical for the support of biodiversity and ecosystem functions. Organic vs. mineral soil layer classifications, hydrologic regime and vegetation indicators have been used to distinguish fens from wet meadows, but complex interactions between physical and environmental variables can make identifying wetland types challenging. Understanding the differences between wetland types is vital for conservation efforts, increasingly so due to the threat of climate-driven changes to the persistence of wetlands. I compared the soils, hydrologic regime, and vegetation composition of groundwater fed wetlands in Rocky Mountain National Park to examine current soil and hydrology-based criteria for distinguishing fens from wet meadows, and to formulate predictions about impacts to these wetlands from climate changes. A three-stage Generalized Random Tessellation Stratified design paired with hand selection was used to identify 45 fens and 55 wet meadows for sampling and one 16m2 plot per site was used to collect vegetation species composition and cover data. The plot was centered on a groundwater monitoring well, measured manually or with an automatic data logger, and the water table variations were compared to local precipitation patterns. The soil profile was described and soil samples were collected at 40 cm depth to determine percent organic matter. Four distinct hydrologic regimes were identified that corresponded to differences in peat thicknesses. Precipitation influences between wetlands and a classification of 12 plant communities were correlated with differences in water table depth, peat thickness, organic matter content, and elevation. No evidence was found to support the use of the existing National Resource Conservation Service (NRCS) Soil Taxonomy distinction between organic and mineral soil layers as a criterion for distinguishing fens from wet meadows. Rather the use of ≥20 cm of peat accumulation was useful for identifying sites with fen vegetation and hydrologic regime. Fen water tables remain within 40 cm of the soil surface while for wet meadows a seasonal water table near the soil surface is sufficient. Many fens and wet meadows had multiple water sources, unrelated to wetland type, each of which influenced their hydrologic regime. Wetlands dominated by groundwater or snow melt inputs may be impacted by climate driven changes in total annual snowpack, longer summer season, and increased summer temperatures, while those influenced by seasonal precipitation will also be affected by changes in the timing, duration, and amount of summer precipitation. Most wetlands are expected to exhibit drying, decreases in peat thickness, and loss of wetland vegetation.
Department Head: N. LeRoy Poff.
Keywords: Hydrologic cycle -- Colorado -- Rocky Mountain National Park; Fens -- Ecology -- Colorado -- Rocky Mountain National Park; Wet meadow ecology -- Colorado -- Rocky Mountain National Park